Proses Desain Kursi dengan Memanfaatkan Modul Silinder dari Bonggol Jagung - Priskila Indah Saptorini; Andry Masri (Jurnal Desain Indonesia., 2020)
One of the results of the exploration of corncobs is a cylindrical module. In this research, the cylindrical module will be used as a component in the chair, so that the search for the right technique and appropriate design will be made so that it can become a strong unit to be used as a chair. So, the purpose of this design process is to produce an appropriate chair design and in accordance with the techniques in utilizing cylindrical corncobs module, to get a compromise value from the novelty with module assembly techniques that must be able to function properly. The role of research for Design Project 5 and Professional Work is to find and test the material of corn cobs woven with rope as a component of a chair's seat base. The research method used was an experiment. The results showed a novelty and obtained a product made from corncobs in the form of a cylinder that can function well as a chair component.